Vanadato de bismuto sintetizado por combustão em solução na presença de diferentes combustíveis: síntese, caracterização e estudo da atividade fotocatalítica - Serafim, Jéssica Aparecida; Afonso, Renata; Lucilha, Adriana Campano; Oliveira, Lucas Agostinho De; Silva, Paulo Rogério Catarini Da; Silva, Marcelo Rodrigues Da [UNESP]; Sartori, Elen Romão; Dall'antonia, Luiz Henrique (Sociedade Brasileira de Química, 2014)
In this manuscript, a BiVO4 semiconductor was synthesized by solution combustion synthesis using different fuels (Alanine, Glycine and Urea). Also, the Tween® 80 surfactant was added during synthesis. BiVO4 was characterized by XRD, SEM and diffuse reflectance spectroscopy. Photocatalytic activity was evaluated by the discoloration of methylene blue at 664 nm under UV-visible light irradiation. According to XRD, the monoclinic phase of BiVO4 was obtained for the samples. The smallest particle size and highest k obs value were observed for the BiVO4/alanine sample, which promoted greater demethylation of methylene blue.
Bismuth vanadate synthesized by solution combustion with different fuels: synthesis, characterization and study of photocatalytic activity
Keywords: BiVO4; photocatalysis; semiconductor